Melt-Blended Multifunctional PEEK/Expanded Graphite Composites - Mokhtari, Mozaffar; Archer, Edward; Bloomfield, Noel; Harkin-Jones, Eileen; Mcilhagger, Alistair (Frontiers in Materials, 2021)
In this work, antistatic, high-performance composites of poly (ether ether ketone) (PEEK) and concentrations of 0.5-7 vol% expanded graphite were fabricated via twin-screw extrusion and injection moulding at mould temperatures of 200 °C. The morphological, electrical, rheological, thermal, mechanical, and wear properties of the composites were investigated. Scanning electron microscope (SEM) images indicate that distribution and dispersion of EG platelets in the PEEK matrix are enhanced at higher EG loadings. The electrical conductivity of the composites with 5 vol% of EG exhibit a sharp rise to the electrical conductivity range of antistatic materials because of the formation of conductive paths. The formation of a three-dimensional EG network led to a rapid increase in the storage modulus of the melt of the 2 vol% of EG loaded composite at a frequency of 0.1 rad/s and temperature of 370 °C. The neat PEEK and composites containing 0.5-5 vol% EG indicated a cold crystallization peak in the first heating scan of a non-isothermal differential scan calorimetry (DSC) test and their crystallinity degrees changed slightly. However, after removing their thermal and stress histories, the EG platelets promoted nucleation and increased the PEEK crystallinity remarkably, indicating that annealing of the PEEK composites can improve their mechanical performance. The neat PEEK exhibits the standard tensile and flexural stress-strain behaviour of thermoplastics, and the composites exhibit elastic behaviour initially followed by a weak plastic deformation before fracture. The addition of 5 vol% of EG to PEEK increased the tensile and flexural modulus from 3.84 and 3.55 GPa to 4.15 and 4.40 GPa, decreased the strength from 96.73 and 156.41 MPa to 62 and 118.19 MPa, and the elongation at break from 27.09 and 12.9 % to 4 and 4.6 % respectively. The wear resistance of the composite containing 3 vol% EG was enhanced by 37% compared with the neat PEEK.